Penerapan Teknologi Tepat Guna Alat Pengaduk Kecap Otomatis untuk UMKM - Rohmah, Ratnasari Nur; Asyari, Hasyim; Nandiroh, Siti; H. Purwoto, Bambang; Bayu Annawawi, Anggesti (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2024)
Soy sauce is one of the most favorite food products of Indonesian people. These food products are widely available in various brands and are produced by both large industries and small and medium businesses. This community service aims to help one of the MSMEs, CV. Selok Jaya, in implementing appropriate technology in its soy sauce production activities. This community service is implemented on the P2TTG scheme service activities, which is the research results application in real life. The device developed in this community service is a PLC-based automatic soy sauce mixer. This device is intended to help the process of cooking soy sauce ingredients more efficient and safer for employees. Community service is carried out in four stages and has been successfully conducted. Partners gave positive response to the activities that had been carried out. The device has been successfully implemented and based on the results of questionnaires and partner interviews, it can be concluded that the device provides benefits for partners, in time efficiency, cleanliness and safety (reducing the risk of injury). On this occasion, partners also suggested that academic activities that support/help MSMEs be further improved.